DNA recombinant molecules carrying different allels of human preproinsulin gene as mutagens in Chinese hamster cells - Rubashevsky, E.L.; Patskovsky, Y.V.; Kirilenko, S.D.; Varzanova, I.S.; Bogolyubova, O.M.; Lysenko, O.F.; Lukash, L.L. (Биополимеры и клетка, 1996)
In our earlier investigations it was discovered the nuttagenic activity of two recombinant plasmids (pBR322ins and pAins) containing the human preproinsulin gene in cultivated somatic mammalian cells. The preproinsulin gene (allel-1) was able to function under its own promoter in different cell types since it lacked a regulatory element providing tissue-specific expression. Introduction of a frameshift mutation into the region of initiation of the translation of the transgene (allel-2) diminished the mutagenic effect of a corresponding recombinant plasmid on gene level. In this work the mutagenic activity of the recombinant plasmids carrying allel-1 (pBR322ins) andallel-2 (pBR322insN) of the preproinsulin gene was studied using cytogenetic test. It was shown that the presence of allel-2 (that probably had altered expression of the transgene) in the recombinant plasmid structure decreased the level of induced chromosome breaks per cell. It was made a conclusion that not only viruses and their genes but also recombinant DNAs of nonviral origin are able to induce chromosome and gene mutations in mammalian cells. The mutagenic activity of studied recombinant plasmids depends on the level of expression of the transgenes in the cells. У наших попередніх дослідженнях було відкрито мутагенну активність двох рекомбінантних плазмід (pBR322ins та pAins), які несуть ген препроінсуліну людини, у соматичних клітинах ссавців, що культивуються. Ген препроінсуліну (алель-1) має здатністьфункціонувати під своїм власним промотором у різних типах клітин, оскільки втратив регуляторний елемент, який забезпечує тканинну специфічність експресії. Введення мутації зсуву рамки зчитування в район ініціації трансляції трансгена (алель-2) призводило до зменшення мутагенного ефекту відповідної рекомбінантної плазміди на генному рівні. У цій роботі вивчалась мутагенна активність рекомбінантних плазмід, що несуть алель-1 (pBR322ins) та алель-2 (pBR322insN) гена препроінсуліну, з використанням цитогенетичного тесту. Показано, що присутність алеля-2 (який, можливо, має пошкодження експресії трансгена) у структурі рекомбінантної плазміди призводить до зниження рівня хромосомних розривів на клітину. Зроблено висновок стосовно того, що не тільки віруси та їх гени, а й рекомбінантні ДНК невірусної природи здатні індукувати хромосомні та генні мутації у клітинах ссавців. Мутагенна активність досліджуваних рекомбінантних плазмід залежить від експресії трансгенів у клітинах. В наших предыдущих исследованиях была обнаружена мутагенная активность двух рекомбинантных плазмид (pBR322ins и pAins), содержащих ген инсулина человека, в культивируемых соматических клетках млекопитающих. Ген инсулина (аллель-1) способен функционировать под своим собственным промотором в различных типах клеток, поскольку утратил регуляторний элемент, обеспечивающий тканеспецифичность экспрессии. Введение мутации сдвига рамки считывания в район инициации трансляции трансгена (аллель-2) приводило к снижению мутагенного эффекта соответствующей рекомбинантной плазмиды на генном уровне. В этой работе изучена мутагенная активность рекомбинантных плазмид, несущих аллель-1 (pBR322ins) и аллель-2 (pBR322insN) гена препроинсулина, с использованием цитогенетического теста. Показано, что присутствие аллеля-2 (имеющего, вероятно, поврежденную экспрессию трансгена) в структуре рекомбинантной плазмиды, вызывало снижение уровня хромосомных разрывов на клетку. Сделан вывод о том, что не только вирусы и их гены, а также рекомбинантные ДНК невирусной природы способны индуцировать хромосомные и генные мутации в клетках млекопитающих. Мутагенная активность исследуемых рекомбинантных плазмид зависит от экспрессии трансгенов в клетках.